Физика как элемент культуры - Тарароев, Яков Владимирович (НТУ "ХПИ", 2015)
Основная задача данной работы – в общих чертах показать (на примере физики) процесс взаимодействия естественнонаучного знания, с развитием культуры в целом и доказать тезис, что естественнонаучное знание, несмотря на то, что объектом его изучения является природа, само выступает элементом человеческой культуры в самом широком смысле этого понятия.

This paper considers the problem of physical knowledge from the perspective of cultural studies. Pointed out that culture is a system of symbols, both material and spiritual. The system of these characters being developed and improved, having three "cultural revolution": Neolithic, urban and industrial. It is shown that the physics, as well as a scientific discipline is a system of symbols. As a tangible symbol can be considered an empirical component of physical knowledge, as spiritual – theoretical. Their unity that had developed as a result of the development of scientific and technological progress and industrial revolution makes physics a full part of human culture. Without science, the modern world would lose its very nature and modern society its future. Right from the start, physics forms the core of European scientific development.
Physics as a culture element
Keywords: символ; неолитическая революция; городская революция; индустриальная революция; физика; эмпирическое; теоретическое; научно-технический прогресс; culture; symbol; Neolithic revolution; urban revolution; industrial revolution; physics; empirical; theoretical; scientific and technical progress